The Gut Microbiome: Bench to Table - Wu, Vivian C. H. (CRC Press, 2022)
The influence of the gut microbiome on human health and disease has been established in recent years through advances in high-throughput DNA sequencing. The Gut Microbiome: Bench to Table presents a scientific introduction to this topic and analyzes the research on how the microbiome is affected by nutrients and how dietary modifications can alter the microbiome. The Gut Microbiome: Bench to Table is divided into three sections. The first section details the current state of laboratory-scale analysis of gut microbiome samples and how we can identify the communities and their functional repertoire. Section II explains the next phase of translational research models such as preclinical animal studies, proof of concept safety, and efficacy human trials. The third section demonstrates the effectiveness of therapeutic treatments in larger populations. It addresses how diet influences the gut microbiome and presents an array of approaches that have been reported, including a discussion of issues of the safety of probiotics and selected supplements and micronutrients. This book is essential for clinicians, dietitians, and food and nutrition professionals who wish to have the most up-to-date knowledge in understanding gut microbiome and diet.